Analisis Struktur Mikro (Retoris) dalam Novel Begjane Rustam Karya Pak Met - Rahma Surya Kusuma Putri; Budi Waluyo; Rahmat Rahmat (Universitas Sebelas Maret, 2023)
In the process of analyzing prose narratives such as novels, they often encounter difficulties due to relatively less interest in reading and the time spent reading is longer and boring. In order to overcome these difficulties, a critical discourse analysis strategy is used to assist in understanding literary works. The research method in this research is descriptive qualitative research that uses a critical discourse analysis approach to the Teun A. Van Dijk model. This study uses one level of critical discourse analysis of the Teun A. Van Dijk model, namely the micro (rhetorical) structure. The source of the data used in this research is a document, namely the novel Begjane Rustam by Pak Met. The purpose of this study is to describe the microstructure of the rhetorical aspects contained in Pak Met's Begjane Rustam novel. The results show that Begjane Rustam's novel contains three rhetorical aspects, namely 1) graphic elements are shown in the use of italics and bold print, 2) metaphorical elements are shown in the use of figurative language (majas), and 3) expression elements are shown in the depiction of character expressions. directly by the author. It can be concluded that Pak Met's Begjane Rustam novel includes three rhetorical aspects (microstructure) namely graphics, metaphors, and expressions.